Vision for Functionally Decorated and Molecularly Imprinted Polymers in Regenerative Engineering - Clegg, John R. (Regen Eng Transl Med, 2017)
The emerging field of regenerative engineering offers a great challenge and an even greater opportunity for materials scientists and engineers. How can we develop materials that are highly porous to permit cellular infiltration, yet possess sufficient mechanical integrity to mimic native tissues? How can we retain and deliver bioactive molecules to drive cell organization, proliferation, and differentiation in a predictable manner? In the following perspective, we highlight recent studies that have demonstrated the vital importance of each of these questions, as well as many others pertaining to scaffold development. We posit hybrid materials synthesized by molecular decoration and molecular imprinting as intelligent biomaterials for regenerative engineering applications. These materials have potential to present cell adhesion molecules and soluble growth factors with fine-tuned spatial and temporal control, in response to both cell-driven and external triggers. Future studies in this area will address a pertinent clinical need, expand the existing repertoire of medical materials, and improve the field’s understanding of how cells and materials respond to one another.